Directions for Improving State Policy to Form and Strengthen the Export Potential of Agricultural Products - Bagirzadeh, A. (Економічний вісник Донбасу, 2021)
The main purpose of the study is to analyze the current state of agricultural production, explore processing opportunities and identify areas for improving public policy to increase export potential. A statistical, systematic approach, analysis and generalization methods were used in the research work. The article provides an analysis of the role of the state in increasing the production of export-oriented agricultural products, improving competitiveness and quality, improving the technological capabilities of milk and dairy products, cotton, meat and meat products, tobacco, grapes.
The research analyzes the directions of improving the state policy in increasing the production of science-intensive products by providing import-substituting agricultural products and applying scientific and technical progress. The article examines the opportunities to increase the production of agricultural products, evaluates the activities of processing enterprises, analyzes the processing potential in this area and identifies areas of state support in this area. The study analyzes the interaction of these areas, development prospects and export opportunities, and makes relevant proposals on the effectiveness and development of measures. Основною метою дослідження є аналіз поточного стану сільськогосподарського виробництва, вивчення можливостей переробки та визначення напрямів удосконалення державної політики для підвищення експортного потенціалу. У роботі використовувалися статистичний, системний підхід, методи аналізу та узагальнення. У статті проводиться аналіз ролі держави у збільшенні виробництва експортоорієнтованої сільськогосподарської продукції, підвищенні конкуренто¬спроможності та якості, покращенні технологічних можливостей виробництва молока та молочних продуктів, бавовни, м'яса та м'ясопродуктів, тютюну, винограду.
У дослідженні проаналізовано напрями вдосконалення державної політики у галузі збільшення виробництва наукомісткої продукції за рахунок забезпечення імпортозамінною сільськогосподарською продукцією та застосування науково-технічного прогресу. У статті розглядаються можливості збільшення виробництва сільськогосподарської продукції, дається оцінка діяльності переробних підприємств, аналізується переробний потенціал у цій сфері та визначаються напрями державної підтримки у цій сфері. У дослідженні аналізується взаємодія цих напрямів, перспективи розвитку та експортні можливості, а також вносяться відповідні пропозиції щодо ефективності та розвитку заходів. Основной целью исследования является анализ текущего состояния сельскохозяйственного производства, изучение возможностей переработки и определение направлений совершенствования государственной политики для повышения экспортного потенциала. В работе использовались статистический, системный подход, методы анализа и обобщения. В статье проводится анализ роли государства в увеличении производства экспортоориентированной сельскохозяйственной продукции, повышении конкурентоспособности и качества, улучшении технологических возможностей производства молока и молочных продуктов, хлопка, мяса и мясопродуктов, табака, винограда.
В исследовании проанализированы направления совершенствования государственной политики в области увеличения производства наукоемкой продукции за счет обеспечения импортозамещающей сельскохозяйственной продукцией и применения научно-технического прогресса. В статье рассматриваются возможности увеличения производства сельскохозяйственной продукции, дается оценка деятельности перерабатывающих предприятий, анализируется перерабатывающий потенциал в данной сфере и определяются направления государственной поддержки в данной сфере. В исследовании анализируется взаимодействие этих направлений, перспективы развития и экспортные возможности, а также вносятся соответствующие предложения по эффективности и развитию мероприятий.